(untitled) (Trabalho & Educação, 2016)
This paper deals with the role that high school education plays in the formation of workers, in view of its integration into the working world. Take a theoretical and methodological reference of historical materialism in parallel to the case study done with two companies that are in the most dynamic end of the production chain in the manufacturing sector of automotive vehicles of Curitiba and Greater Region. The question that guided the research was: the completion of high school has favored worker insertion in industries that are in the most dynamic end of the production chain? After analyzing the type of work performed in the production line, as well as the criteria for selecting and hiring workers, it was evident that high school is mediate requirement, not immediately, for entering the most dynamic companies in the chain, where the experience is decisive; high school general education, in these companies, is the cutoff point in the selection process. ___ Este texto trata da função desempenhada pelo Ensino Médio na formação dos trabalhadores, tendo em vista sua inserção no mundo do trabalho. Toma por referência teórica e metodológica o materialismo histórico e se apoia num estudo de caso realizado em duas empresas que se situam na ponta mais dinâmica da cadeia produtiva no ramo de fabricação de veículos automotores de Curitiba e região metropolitana. A questão que norteou a pesquisa foi: a conclusão do Ensino Médio tem favorecido a inserção do trabalhador nas indústrias que se encontram na ponta mais dinâmica da cadeia produtiva? Após analisar o tipo de trabalho executado na linha de produção, bem como os critérios de seleção e contratação de trabalhadores, evidenciou-se que o Ensino Médio é um requisito relevante para o ingresso nas empresas mais dinâmicas da cadeia, mas não o fator decisivo, que é a experiência. A exigência de conclusão do Ensino Médio se dá, principalmente, como ponto de corte nos processos seletivos e pela expectativa de possibilitar ao trabalhador condições para participar dos treinamentos internos.